Peran Literasi Informasi dalam Meningkatkan Mutu Pendidikan Menuju 5.0 - Fitrih Aulia Salam; Bahrani, Bahrani (CV. ITTC INDONESIA, 2025)
In the era of Society 5.0, education is required to adapt to the rapid advancement of technology and information. Information literacy has become an essential competency for both teachers and students, enabling them to filter, evaluate, and utilize information critically and effectively. Through a review of Indonesian research, this article analyzes the role of information literacy in improving the quality of education. The findings indicate that information literacy has a significant impact on academic performance, critical thinking, and learning-related decision-making. Within the school context, the integration of information literacy through curriculum design, library services, and teacher training has strong potential to enhance educational quality in the 5.0 era. Recommendations include strengthening policies, optimizing library functions, and improving information literacy among teachers and students.